2018
DOI: 10.1109/jphotov.2018.2871329
|View full text |Cite
|
Sign up to set email alerts
|

Dry Passivation Process for Silicon Heterojunction Solar Cells Using Hydrogen Plasma Treatment Followed by <italic>In Situ</italic> a-Si:H Deposition

Abstract: A fully dry and hydrofluoric-free low-temperature process has been developed to passivate n-type crystalline silicon (c-Si) surfaces. Particularly, the use of a hydrogen (H 2 ) plasma treatment followed by in situ intrinsic hydrogenated amorphous silicon (a-Si:H) deposition has been investigated. The impact of H 2 gas flow rate and H 2 plasma processing time on the a-Si:H/c-Si interface passivation quality is studied. Optimal H 2 plasma processing conditions result in the best effective minority carrier lifeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Besides, Liu et al [135] found that the post H 2 plasma treatment with residual SiH 4 molecules contributes to the formation of a dense silicon layer which can inhibit the out diffusion of hydrogen from bulk, thus, causing evident enhancement in the J sc , V oc and E ff of SHJ solar cells. Xu et al [136] also demonstrated that microwave H 2 plasma treatment before a-Si:H deposition can effectively reduce surface recombination velocity as low as 4 cm s −1 .…”
Section: Huge Benefits Of Hydrogenation On Next-generation Silicon So...mentioning
confidence: 99%
“…Besides, Liu et al [135] found that the post H 2 plasma treatment with residual SiH 4 molecules contributes to the formation of a dense silicon layer which can inhibit the out diffusion of hydrogen from bulk, thus, causing evident enhancement in the J sc , V oc and E ff of SHJ solar cells. Xu et al [136] also demonstrated that microwave H 2 plasma treatment before a-Si:H deposition can effectively reduce surface recombination velocity as low as 4 cm s −1 .…”
Section: Huge Benefits Of Hydrogenation On Next-generation Silicon So...mentioning
confidence: 99%
“…13,14 Extrinsic hydrogenation method like hydrogen plasma treatment (HPT) for Si HJ has been considered one of the industrially viable schemes to reduce deep and shallow defect states in the a-Si:H/c-Si hetero-interface. 15 Different groups have studied the introduction of HPT at various stages of amorphous silicon deposition, namely, Pre 16 (before i-layer), Post 17 (after i-layer), and Intermediate (during i-layer) HPT 15 using either R.F. (radio-frequency) or very-high frequency (V.H.F) PECVD methods.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Different groups have studied the introduction of HPT at various stages of amorphous silicon deposition, namely, Pre (before i-layer), Post (after i-layer), and Intermediate (during i-layer) HPT using either R.F. (radio-frequency) or very-high frequency (V.H.F) PECVD methods. , Comparative studies of different HPT methods , have shown that I-HPT and Post-HPT show better performance because they prevent defect generation due to ion-bombardment on free Si surface during Pre-treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In general, optimized (i)a-Si:H should be deposited with dense bulk quality while suppressing the detrimental epitaxial growth at the c-Si/(i)a-Si:H interface. 3 Approaches have been proposed to enhance the surface passivation qualities of (i)a-Si:H layer, such as using hydrogendiluted SiH 4 , [4][5][6][7] pre-or post-hydrogen plasma treatment (HPT), [8][9][10][11][12][13][14][15] (i) a-Si:H bilayer stacks 5,[16][17][18][19][20][21][22] and post-annealing. 3,23,24 Subsequent overlaying of doped layers and transparent conductive oxide (TCO) on the (i)a-Si:H layers also impose challenges on preserving their passivation qualities of the c-Si surface.…”
mentioning
confidence: 99%